Current Legal Issues Affecting Central Banks, Volume I. (International Monetary Fund, 1992)
Edited by Robert C. Effros, this first volume in a new series for attorneys, economists, financial managers, and the general public is based on biennial IMF seminars held for central bank general counsels. Among the topics analyzed by international banking and legal experts are jurisprudence concerning the IMF's Articles of Agreement; the debt crisis; investment dispute settlement; banking regulation, deregulation, supervision, and secrecy; electronic fund transfers (EFTS); the Basle Concordat; sovereign immunity of central banks; and Islamic banking.